Dissipation Element Analysis of Turbulent Premixed Jet Flames. Issue 9 (2nd September 2019) - Denker, D.; Attili, A.; Luca, S.; Bisetti, F.; Gauding, M.; Pitsch, H.
ABSTRACT: Dissipation element (DE) analysis is a method for analyzing scalar fields in turbulent flows. DEs are defined as a coherent region in which all gradient trajectories of a scalar field reach the same extremal points. Therefore, the scalar field can be compartmentalized in monotonous space-filling regions. The DE analysis is applied to a set of spatially evolving premixed jet flames at different Reynolds numbers. The simulations feature finite rate chemistry with 16 species and 73 reactions. The jet consists of a methane/air mixture with an equivalence ratio φ  = 0.7. Statistics of DE parameters are shown and compared to those of a DNS of a non-reacting spatial jet, a non-reacting temporally evolving jet and isotropic homogeneous turbulence. The invariance of the normalized length distribution of the DEs toward changes in Reynolds number observed in non-reacting flows holds for the reacting cases and the characteristic scaling with Kolmogorov micro-scale is reproduced. Furthermore, the DE statistics reflect the influence of the premixed flame structure on the turbulent scalar fields.